Benin : Fifth Review Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
Following satisfactory economic and financial performance under the Poverty Reduction and Growth Facility-supported program, performance was mixed. Benin should pursue a prudent debt-management policy with the support of the newly created debt committee. Implementation of the structural reform agenda is of critical importance for achieving the objectives of the Poverty Reduction Strategy Paper. Strengthening of the financial sector and maintaining external debt on a sustainable path is needed in Benin. Risks to the medium-term program remain, but they are manageable.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet